Intersecting Social and Political Struggles Beyond the Margins: Voices from Israeli Mizrahi Feminists - Daniele, G. (PSA (Political Studies Association) Annual Conference, University of York - UK, 2022)
This paper intends to analyse the status “in-between” of Israeli Mizrahi feminist activists and their socio-political role in creating alternative forms of grassroots politics and everyday resistance from the margins of Israeli society. Such a perspective calls into question several examples of intra-Jewish asymmetric power relations, through the framework of settler colonialism on the one hand and intersectionality on the other. Founded on extensive fieldwork, this paper explores the Mizrahi feminist outlook that has stressed the importance to address the needs of women who live in marginalised conditions and suffer both individual oppression because of their gender and collective oppression for belonging to underprivileged communities. As one of the most significant cases of Mizrahi feminist activism, since the late 1990s the organisation called Achoti (Sister) - for Women in Israel has dealt with the meaning of sisterhood in multiethnic and multicultural societies. Based mainly in south Tel Aviv, and following the principles of “feminism of colour”, they have represented an alternative way of looking at and questioning Israeli society beyond the margins. By deeply connecting women coming from differentiated marginalised socio-political backgrounds, including also Palestinians, Bedouins, Ethiopians, Russians and, more recently, African refugees from Eritrea and Sudan, they have united common struggles led by the poorest and most underrepresented actors within Israel. In the attempt to balance local and grassroots politics, this can be considered as a challenging field of study needing to be analysed more in depth and related to the major subject matters concerning intersectional politics from and beyond the margins of different contexts across the world.